Persistent oral mucosal lesions preceding diagnosis of Crohn's disease and primary sclerosing cholangitis - Nylund Karita; Helenius-Hietala Jaana; Åberg Fredrik; Hagström Jaana; Ruokonen Hellevi (WILEY, 2025)
Oral mucosal lesions may persist years before symptoms or diagnosis of inflammatory bowel disease (IBD) and subsequent primary sclerosing cholangitis (PSC). Since a dental practitioner may be the first clinician to suspect IBD with extraintestinal manifestations (EIMs), early referral, and close collaboration with a gastroenterologist are recommended.